Digital microwave communication : engineering point-to-point microwave systems - Kizer, George M. (George Maurice), 1945- (Piscataway, NJ : IEEE Press ; Hoboken, New Jersey : Wiley, 2013)
"Until now, no book has adequately treated all engineering aspects of microwave communications in the digital age. This important new work provides readers with the depth of knowledge necessary for all the practical engineering details associated with fixed point-to-point microwave radio path design: the why, what, and how of microwave transmission; design objectives; engineering methodologies; and design philosophy (in the bid, design, and acceptance phase of the project). Written in an easily accessible format, the book is complete with an appendix of specialized engineering details and formulas.?"--
"Integrated use of industry leading microwave path engineering software to solve problems introduced in the book"--
1. A Brief History of Microwave Radio Fixed Point-to-Point (Relay) Communication Systems -- 2. Regulation of Microwave Radio Transmissions -- 3. Microwave Radio Overview -- 4. Radio Network Performance Objectives -- 5. Radio System Components -- 6. Designing and Operating Microwave Systems -- 7. Hypothetical Reference Circuits -- 8. Microwave Antenna Theory -- 9. Multipath Fading -- 10. Microwave Radio Diversity -- 11. Rain Fading -- 12. Ducting and Obstruction Fading -- 13. Reflections and Obstructions -- 14. Digital Receiver Interference -- 15. Network Reliability Calculations -- 16. Path Performance Calculations -- A. Microwave Formulas and Tables -- B. Personnel and Equipment Safety Considerations.
Includes bibliographical references and index.
Print version record and online resource.
Keywords: Microwave communication systems; Digital communications; TECHNOLOGY & ENGINEERING -- Microwaves; TECHNOLOGY & ENGINEERING -- Telecommunications; Digital communications; Microwave communication systems; Electronic books